Effect Of Plyometric Training on Long Jump Ability - Sutan Irvan Charis; Alex Aldha Yudi; Sari Mariati (Universitas Negeri Padang, 2019)
This study discusses plyometric exercises in improving the long jump ability of self-development students of SMAN 1 Batang Anai. The purpose of this study was to describe the process and results of conducting plyometric exercises of 16 meetings for the long jump ability of the self-improvement students of SMAN 1 Batang Anai Padang Pariaman. the type of research used is quasi-experimental research. The design of this study is one group pre-test-posttest design. The study population was students who participated in athletic self-development activities at SMAN 1 Batang Anai Padang Pariaman, amounting to 16 people. The sampling technique in this study used a Census Sampling of 16 people. The exercises are given 4 times per week for 16 meetings. The instrument used is the long jump. Data analysis using t-test. Based on the results of research conducted it can be concluded that there is a significant influence of plyometric exercises on increasing the ability of long jump self-development students of SMAN 1 Batang Anai Padang Pariaman, where tcount = 3.64> ttable = 1.74. The average long jump ability of a student's initial test is 3.64 and the average long jump ability of a student's final test is 4.15.